What you need to know about irregular verbs (Learners Pub., 2004)
This book covers 160 of the most important irregular verbs that learners have to understand in order to be able to use their past and perfect tenses correctly. The book highlights the irregular parts of these verbs, defines their meanings and shows their correct uses.